Perbandingan Hukum Perdata di Negara-Negara Asean Kajian Terhadap Perbandingan Indonesia dan Malaysia - Ariel Lois; Handar Subhandi Bakhtiar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the comparative analysis of civil law systems between Indonesia and Malaysia, which adhere to the Civil Law and Common Law systems, respectively. Indonesia implements the Civil Law system, inherited from Dutch colonial rule and based on the Burgerlijk Wetboek (BW), whereas Malaysia adopts the Common Law system, derived from the English legal tradition. The fundamental difference between these systems lies in their sources of law, where Civil Law prioritizes codification through written statutes, while Common Law relies on jurisprudence and judicial precedents. Additionally, Malaysia employs a mixed legal system, incorporating elements of Customary Law and Islamic Law in specific legal matters. This study further explores the potential for harmonization of civil law between Indonesia and Malaysia through the Private International Law (PIL) framework, which facilitates cross-border dispute resolution based on the lex patriae and lex domicilii principles. By employing a Juridical-Normative methodology and adopting Comparative, Analytical, and Conceptual approaches, this research underscores the significance of understanding legal system differences to enhance legal cooperation between the two nations.